Image-guided simulation of tissue deformation using a mechanical model on a surgical application. Issue 2 (25th January 2017) - Nguyen, Toan B.; Huang, Albert Y.; Fikfak, Vid; Dunkin, Brian J.; Garbey, Marc
Abstract: This paper presents a method for localizing the position of a liver and a tumor within the tissue during a minimally invasive liver operation. From pre-operative CT scans, the liver volume and its internal structures are segmented using image-processing techniques. Based on these segmentations, a three-dimensional mechanical model is built to compute the liver volume and internal structure displacement under boundary conditions such as external forces from the surgical instrument. This can help the surgeon understand the motion of internal structures when manipulating the liver. To validate our method, an experiment on a porcine liver explant was performed to assess the difference between actual tissue motion and the mechanical model.